A Horizon Scan of Emerging Issues for Global Conservation in 2019. (January 2019) - Sutherland, William J.; Broad, Steven; Butchart, Stuart H.M.; Clarke, Stewart J.; Collins, Alexandra M.; Dicks, Lynn V.; Doran, Helen; Esmail, Nafeesa; Fleishman, Erica; Frost, Nicola; Gaston, Kevin J.; Gibbons, David W.; et al.
Abstract : We present the results of our tenth annual horizon scan. We identified 15 emerging priority topics that may have major positive or negative effects on the future conservation of global biodiversity, but currently have low awareness within the conservation community. We hope to increase research and policy attention on these areas, improving the capacity of the community to mitigate impacts of potentially negative issues, and maximise the benefits of issues that provide opportunities. Topics include advances in crop breeding, which may affect insects and land use; manipulations of natural water flows and weather systems on the Tibetan Plateau; release of carbon and mercury from melting polar ice and thawing permafrost; new funding schemes and regulations; and land-use changes across Indo-Malaysia. Highlights: We present the 15 topics identified in our tenth annual horizon scan for global conservation. Scoring was carried out by a diverse group of experts using a Delphi-like process. Scores were based on the topics' novelty, likelihood, and potential for major impacts on biodiversity. Emerging themes include conservation impacts of biotechnological advances in agriculture. Other issues included climate change-induced release of carbon and mercury from polar ice.